Rapid Boosting of HIV-1 Neutralizing Antibody Responses in Humans Following a Prolonged Immunologic Rest Period. (4th January 2019) - Spearman, Paul; Tomaras, Georgia D; Montefiori, David C; Huang, Ying; Elizaga, Marnie L; Ferrari, Guido; Alam, S Munir; Isaacs, Abby; Ahmed, Hasan; Hural, John; McElrath, M Juliana; Ouedraogo, Laissa; et al.
Abstract: Background: The durability and breadth of human immunodeficiency virus type 1 (HIV-1)–specific immune responses elicited through vaccination are important considerations in the development of an effective HIV-1 vaccine. Responses to HIV-1 envelope subunit protein (Env) immunization in humans are often described as short-lived. Methods: We enrolled 16 healthy volunteers who had received priming with an HIV-1 subtype B Env vaccine given with MF59 adjuvant 5–17 years previously and 20 healthy unprimed volunteers. Three booster immunizations with a heterologous subtype C trimeric gp140 protein vaccine were administered to the primed group, and the same subtype C gp140 protein vaccination regimen was administered to the unprimed subjects. Results: Binding antibodies and neutralizing antibodies to tier 1 viral isolates were detected in the majority of previously primed subjects. Remarkably, a single dose of protein boosted binding and neutralizing antibody titers in 100% of primed subjects following this prolonged immunologic rest period, and CD4 + T-cell responses were boosted in 75% of primed individuals. Conclusions: These results demonstrate that HIV-1 protein immunogens can elicit durable memory T- and B-cell responses and that strong tier 1 virus neutralizing responses can be elicited by a single booster dose of protein following a long immunologic rest period. However, we found no evidence that cross-clade boosting led to a significantly broadened neutralizing antibody response.